A Comparative Study on Corneal Astigmatism Induced By Superior Versus Temporal Incision In Small Incision Cataract Surgery - Dr. Adapa Venkata Satish, Dr.M.V. Bhavani, Dr.K.Laksmoji Naidu (International Journal of Scientific Research and Management (IJSRM), 2015)
..